Altered Cervical Spinal Cord Resting‐State Activity in Fibromyalgia. Issue 3 (11th February 2019) - Martucci, Katherine T.; Weber, Kenneth A.; Mackey, Sean C.
Abstract : Objective: Altered afferent input and central neural modulation are thought to contribute to fibromyalgia symptoms, and these processes converge within the spinal cord. We undertook this study to investigate the hypothesis that, using resting‐state functional magnetic resonance imaging (rs‐fMRI) of the cervical spinal cord, we would observe altered frequency‐dependent activity in fibromyalgia. Methods: Cervical spinal cord rs‐fMRI was conducted in fibromyalgia patients (n = 16) and healthy controls (n = 17). We analyzed the amplitude of low‐frequency fluctuations (ALFF), a measure of low‐frequency oscillatory power, for frequencies of 0.01–0.198 Hz and frequency sub‐bands to determine regional and frequency‐specific alterations in fibromyalgia. Functional connectivity and graph metrics were also analyzed. Results: As compared to healthy controls (n = 14), greater ventral and lesser dorsal mean ALFF of the cervical spinal cord was observed in fibromyalgia patients ( n = 15) (uncorrected P < 0.05) for frequencies of 0.01–0.198 Hz and all sub‐bands. Additionally, lesser mean ALFF within the right dorsal quadrant (corrected P < 0.05) for frequencies of 0.01–0.198 Hz and sub‐band frequencies of 0.073–0.198 Hz was observed in fibromyalgia. Regional mean ALFF was not correlated with pain; however, regional lesser mean ALFF was correlated with fatigue in patients (r = 0.763, P = 0.001). Functional connectivity and graph metrics were similar between groups. Conclusion: Our results indicate unbalanced activity between the ventral and dorsal cervical spinal cord in fibromyalgia. Increased ventral neural processes and decreased dorsal neural processes may reflect the presence of central sensitization and contribute to fatigue and other bodily symptoms in fibromyalgia.